Neuroprotective Effects of Physical Activity: Evidence from Human and Animal Studies - Chieffi, Sergio; Messina, Giovanni; Villano, Ines; Messina, Antonietta; Valenzano, Anna; Moscatelli, Fiorenzo; Salerno, Monica; Sullo, Alessio; Avola, Roberto; Monda, Vincenzo; Cibelli, Giuseppe; Monda, Marcellino (Frontiers in Neurology, 2017)
In the present article we provide a review of current knowledge regarding the role played by physical activity (PA) in preventing age-related cognitive decline and reducing risk of dementia. The cognitive benefits of PA are highlighted by epidemiological, neuroimaging and behavioral studies. Epidemiological studies identified PA as a influential lifestyle factor in predicting rates of cognitive decline. Individuals physically active from midlife show a reduced later risk of cognitive impairment. Neuroimaging studies documented attenuation of age-related brain atrophy, and also increase of grey matter and white matter of brain areas, including frontal and temporal lobes. These structural changes are often associated with improved cognitive performance. Importantly, the brain regions that benefit from PA are also those regions that often are reported to be severely affected in dementia. Animal model studies provided significant information about biomechanisms that support exercise-enhanced neuroplasticity, such as angiogenesis and upregulation of growth factors. Among the growth factors, the BDNF seems to play an significant role. Another putative factor that might contribute to beneficial effects of exercise is the neuropeptide orexin-A. The beneficial effects of PA may represent an important resource to hinder the cognitive decline associated with aging.